Correlação entre volume, área e profundidade da orofaringe por meio da tomografia computadorizada volumétrica - Silva, Alexandre Oliveira e (2012)
A volumetric CT scan is a standard and repeatable exam very useful in dentistry. It permits an evaluation of the teeth with the jaws and the jaws with the facial skull including the upper airways. This study's objective was to evaluate the reliability of the sagital images, as in cephalometric radiographs, for the diagnosis of the oropharynx associating it with measurements of areas of larger constriction and the total volume of the oropharynx, obtained on the volumetric CT scan. The sample was composed of images of the volumetric CT scan of thirty individuals. All the measurements were performed using InVivo Dental 5.0 software (Anatomage®, San Jose, Ca, USA). The Pearson correlation coefficient was used to compare the variables of the study. There was a moderate correlation between the linear distance and the areas of larger constriction, and a weaker correlation between the linear distance and the total volume. The sagital measurement (depth) seems less reliable when compared with the values of the smaller area (moderate correlation) and the volume (weak correlation) of the oropharynx, while the area of larger constriction and the volume are strongly correlated.